The God of creation Genesis 1-11 - Epp, Theodore Herman, 1907-1985 (Lincoln, NE Back to the Bible Broadcast, 1972)
Includes photographs.
Originally published in 2 volumes.
Keywords: Bible. O.T. -- history of contemporary events; Creation; Isaac, biblical patriarch -- biography; Bible. O.T. Genesis I-XI -- criticism, interpretation, etc